2019
DOI: 10.3390/antiox8060192
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1, HDL Subclasses and Post Surgery Acute Inflammation: A Pilot Study

Abstract: High density lipoproteins (HDL) structure and function studies are needed to better understand the heterogeneous nature of the HDL particle, and its interaction with associated proteins such as apolipoprotein A-1 (ApoA-1), paraoxonase 1 (PON1) and the environment. Our study assesses the effects of acute inflammation on PON1 and HDL subclasses in post-surgical colorectal cancer patients. PON1 was measured kinetically through its arylesterase and lactonase activity and HDL sub-classes were measured using Quantim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
2
14
0
4
Order By: Relevance
“…Bains et al ( 2019 ) compared PON1 lactonase activity in patients with intestinal cancer before and after treatment. The authors concluded that both arylesterase and DHC lactonase activity significantly decreased after the surgery (compared with before treatment), and then increased again with time (Bains et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bains et al ( 2019 ) compared PON1 lactonase activity in patients with intestinal cancer before and after treatment. The authors concluded that both arylesterase and DHC lactonase activity significantly decreased after the surgery (compared with before treatment), and then increased again with time (Bains et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Параоксонази -це сімейство ензимів, що представлене ПОН-1, ПОН-2 і ПОН-3, які мають широку специфічність і каталітичну універсальність [17,18]. Споріднені ензими ПОН-2 і ПОН-3 були названі за їх еволюційним зв'язком з ПОН-1 [19,20].…”
Section: Original Papersunclassified
“…Численними клінічними дослідженнями продемонстровано взаємозв'язок між зниженням активності ПОН-1 у сироватці та розвитком ССЗ [17]. Зниження активності ПОН-1 запускає ендотеліальну дисфункцію, викликаючи агрегацію тромбоцитів, адгезію моноцитів та підвищення активності NO-синтази [8,17,18]. Зокрема, ПОН-1 каталізує реакції гідролізу окислених компонентів ЛПНЩ, які стимулюють утворення цитокінів та індукують адгезію моноцитів до поверхні ендотеліоцитів [17,18].…”
Section: Original Papersunclassified
See 2 more Smart Citations